Fathers' Perception, Practice, and Challenges in Young Child Care and Feeding in Ethiopia. (September 2016) - Bilal, Selamawit; Spigt, Mark; Czabanowska, Kasia; Mulugeta, Afework; Blanco, Roman; Dinant, GeertJan
Background: The role of fathers in proper nutrition of young children has not been a frequent topic of studies. Mothers are usually the primary caregivers for young children. However, the father is often responsible for the financial choices of the household, especially in developing countries; we wondered to what extent fathers were involved in child feeding. Objective: This study aimed to investigate the extent of perceptions, practices, and challenges of fathers from low-income settings in routine child care, particularly in relation to child-feeding practices. Methods: A qualitative study was conducted in northern Ethiopia. Ten fathers, who had children between 6 and 23 months, were participated in the study. To validate fathers' comments, 10 mothers (from different households) also participated. In-depth interviews and focus group discussions were carried out. A thematic analysis was completed to identify emergent themes within the data. Results: In general, traditional fathers, fathers in transition, and modern fathers are the 3 types of fathers identified based on their perception, practice, and challenges of routine child care and feeding. Conclusion: Our findings provide new insight to the literature in describing fathers' roles and challenges in routine child-care and feeding practices. We have developed a model that could help researchers, programmers, policy makers, and health workers to approach fathers in different child intervention research and plans. Our findings suggest that targeting fathers may be a worthwhile approach and that it seems justifiable to plan interventions involving fathers.